Menonton bengkel teater Rendra - Haryono, Edi. ([Yogyakarta] : Kepel Press, 2005)
History of Bengkel Teater Rendra, a theater group directed by W.S. Rendra, and literary criticism on his works; collection of articles
Includes indexes.
Keywords: Rendra, W.S; Bengkel Teater Rendra; Indonesian drama -- Criticism and interpretation